2017 Physics Education Research Conference Proceedings 2018
DOI: 10.1119/perc.2017.pr.110
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the SCALE-UP model and instructors' perceptions of implementation

Abstract: Recent research has highlighted the need to explore the propagation of innovative teaching strategies. SCALE-UP (StudentCentered Active Learning Environment with Upside-Down Pedagogies) is one such innovative strategy that requires transforming the learning space to support small group work. SCALE-UP is both well-propagated and frequently sustained within departments once it is implemented, possibly due to the investment in a transformed learning space. However, not all instructors and departments reach the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Our stance was inspired by our prior research on instructor's modifications of a popular RBIS called SCALE-UP (Student-Centered Active Learning Environment with Upside-Down Pedagogies), described in more detail below (Beichner et al, 2007). We found that many instructors modified the amount of time spent on lecture, student grouping methods, instructional materials (e.g., quizzes and content slides), and the use of teaching assistants (TAs) (Zamarripa Roman et al, 2017) compared to the model as described in the literature. However, the instructors were led to these changes due to their perceptions of student preparation, personal beliefs and values, and institutional facilitating conditions (i.e., funding allocations and scheduling conflicts).…”
Section: Exploring Instructor's Purposeful Modifications To Rbismentioning
confidence: 99%
“…Our stance was inspired by our prior research on instructor's modifications of a popular RBIS called SCALE-UP (Student-Centered Active Learning Environment with Upside-Down Pedagogies), described in more detail below (Beichner et al, 2007). We found that many instructors modified the amount of time spent on lecture, student grouping methods, instructional materials (e.g., quizzes and content slides), and the use of teaching assistants (TAs) (Zamarripa Roman et al, 2017) compared to the model as described in the literature. However, the instructors were led to these changes due to their perceptions of student preparation, personal beliefs and values, and institutional facilitating conditions (i.e., funding allocations and scheduling conflicts).…”
Section: Exploring Instructor's Purposeful Modifications To Rbismentioning
confidence: 99%